STRATEGI PEMASARAN TERHADAP KEMAJUAN PEMBELIAN DAN PENERAPAN MANAJEMEN STRATEGIK PADA PT. MAYORA INDAH Tbk. - Agus Yudianto; Meddy Nurpratama (Jurnal Ekonomi Integra, 2022)
This type of qualitative descriptive research is a research method that utilizes qualitative data and is described descriptively. This type of qualitative descriptive research is often used to analyze social events, phenomena, or circumstances. This type of qualitative descriptive research displays the results of the data as they are without any manipulation process or other treatment. The research place is in Mayora Indah Tbk (MYOR. Data analysis method is done by comparing existing theories with data obtained from case studies. In this analysis the author directly analyzes the conditions existing in the company, then analyze the differences that occur, and whether the differences involve basic matters, from this analysis it can be concluded about the competitive strategy in the document solution business competition at PT. Mayora tbk and provide suggestions the correct application of competitive strategy in the company. To analyze the competitive strategy in the document solution business competition, the researcher compares the existing conditions in the company with existing theories. The method used to analyze the data is qualitative descriptive analysis method. Because the data taken is the result of natural research where the author participates directly in the research. Marketing strategy is really needed for the progress of sales which is expected to be able to achieve the goals and continuity of the company, which is nothing but increasing turnover and profits. To use media techniques in the virtual world of marketing is indeed very important and to adapt to the digitalization era that was built by stockholders as the implementation of strategies and implementations to win consumers, and this is not easy to do because there are many factors that must be prepared, both technical and software and hard. to support the implementation of marketing strategies and tactics for implementing corporate strategies to achieve profitability. , PT. Mayora developed the M1 to M3 quality system for three consecutive years. Until 2016, Mayora's product quality control system has been implemented until now. They gave the name as Quality Mayora System (QMS). Broadly speaking, QMS includes several processes, including: raw material inspection, supplier audit, production process inspection, final inspection of finished goods, and sensory evaluation tests. The manufacturing technology to the packaging of food and beverages at the Mayora factory mostly uses high-level technology.